Associations of multiple lifestyle behaviors with allergic disease symptoms and sensitization in 9-11-year-old Finnish children - Henna Peltonen; Anna Kaarina Kukkonen; Liisa Korkalo; Mikael Fogelholm; Mika J. Mäkelä; Maijaliisa Erkkola; Henna Vepsäläinen (BMC, 2024)
Abstract Background The increase in allergic diseases in children has coincided with the westernization of lifestyles. Although clustering of modifiable lifestyles has been frequently reported in children, there is limited research on how lifestyle factors collectively contribute to allergic conditions. Our aim was to identify lifestyle clusters among Finnish school-aged children and explore their associations with the prevalence of allergic disease symptoms and sensitization. Methods We used cross-sectional data from the international ISCOLE survey and its Finnish ancillary allergy study conducted in 2012-2013. We studied 148-461 children aged 9-11 years living in the metropolitan area of Finland. Parents completed a questionnaire on their child's allergic disease symptoms, and specific IgE responses from blood samples were analyzed to determine allergic sensitization. Lifestyle factors considered in clustering were moderate-to-vigorous-physical activity (MVPA) and nighttime sleep recorded by accelerometers, screen time inquired via a questionnaire, and healthy and unhealthy dietary patterns from food frequency questionnaire data. Lifestyle clusters were identified using K-means cluster analysis, and their associations with allergic disease symptoms and sensitization were explored using logistic regression models. Results Two distinct and stable clusters were identified: 'healthier lifestyle & lower MVPA' and 'unhealthier lifestyle & higher MVPA'. After adjustments, children in the 'unhealthier lifestyle & higher MVPA' cluster did not show significantly different odds for symptoms of asthma (OR: 0.80, 95% CI: 0.46-1.37), allergic rhinitis (OR: 1.32, 95% CI: 0.77-2.24), or eczema (OR: 0.89, 95% CI: 0.43-1.77) as compared to those in the 'healthier lifestyle & lower MVPA' cluster. Similar results were observed for sensitization to ≥ 1 inhaled allergen (OR: 1.27, 95% CI: 0.53-3.10) and sensitization to ≥ 1 food allergen (OR: 0.91, 95% CI: 0.30-2.60). Conclusions The results suggest that modifiable lifestyle factors may not play a significant role in allergic conditions within the examined age group. Lifestyle behaviors established in earlier childhood may serve as more credible predictors of allergic outcomes.